A spatially hybrid fluid-kinetic neutral model for SOLPS-ITER plasma edge simulations. (May 2019) - Blommaert, Maarten; Horsten, Niels; Börner, Petra; Dekeyser, Wouter
Highlights: A spatially hybrid fluid-kinetic neutral model is implemented in SOLPS-ITER. Interface conditions are presented for neutrals at the outer edge of the plasma grid. Kinetic effects at the outer wall are shown to impact simulation results. The hybrid model captures the kinetic transport effects at the outer wall well. The hybrid transport simulation agrees well with a converged kinetic simulation. Abstract: Plasma edge transport simulations typically rely on Monte-Carlo simulations for the kinetic neutral transport. However, for detached operating conditions the dominance of charge-exchange reactions between plasma and neutrals leads to excessive computational costs of these Monte-Carlo simulations. Since the fluid assumption becomes valid in these highly-collisional conditions, the use of a fluid neutral model is interesting to reduce computational costs. In this paper, we show within the SOLPS-ITER code suite that while our recently developed fluid neutral model is able to accurately represent the neutral transport in the divertor, it is unable to capture the kinetic effects near the outer wall. Due to this model flaw, discrepancies in plasma state arise between the fluid plasma-neutral model and a simulation with kinetic neutrals after converging the model equations. As a solution, we present a spatially hybrid neutral model that captures these kinetic effects near the wall, while benefiting from the fluid approach in the divertor region. Moreover, by using the kinetic code in the region outside the plasma grid, the method is able to accurately account for neutral transport through the voids surrounding the plasma and into pumps. We show on a case with a simplified 'slab' geometry that the results of the proposed hybrid model compare excellently to those of the kinetic solution.